2009
DOI: 10.1093/ntr/ntp050
|View full text |Cite
|
Sign up to set email alerts
|

Illicit drug use as a predictor of smoking cessation treatment outcome

Abstract: Illicit drug use appears to have a significant detrimental effect on the success of an attempt to stop smoking. This effect is not explained by differences between drug users and nonusers on established prognostic factors. These first results in a prospective sample support findings from a large U.S. population survey of smoking cessation rates in drug users and nonusers. If these results are corroborated, clinicians treating smokers should consider developing new protocols to improve outcomes in smokers using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…While this study was not powered to investigate effects on treatment success, many abused drugs are known to increase smoking rates (e.g., cocaine, Roll, Higgins, & Tidey, 1997;alcohol, Griffiths, Bigelow, & Liebson, 1976;opioids, Mello et al, 1980) and interfere with quit attempts in nonpregnant populations (Richter, Ahluwalia, Mosier, Nazir, & Ahluwalia, 2002;Stapleton, Keaney, & Sutherland, 2009), although marijuana use has not been demonstrated to do so (Nemeth-Coslett, Henningfield, O'Keeffe, & Griffiths, 1986). However, we know of one study where marijuana use was correlated with failure to quit smoking during pregnancy (Haskins, Bertone-Johnson, Pekow, Carbone, & Chasan-Taber, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While this study was not powered to investigate effects on treatment success, many abused drugs are known to increase smoking rates (e.g., cocaine, Roll, Higgins, & Tidey, 1997;alcohol, Griffiths, Bigelow, & Liebson, 1976;opioids, Mello et al, 1980) and interfere with quit attempts in nonpregnant populations (Richter, Ahluwalia, Mosier, Nazir, & Ahluwalia, 2002;Stapleton, Keaney, & Sutherland, 2009), although marijuana use has not been demonstrated to do so (Nemeth-Coslett, Henningfield, O'Keeffe, & Griffiths, 1986). However, we know of one study where marijuana use was correlated with failure to quit smoking during pregnancy (Haskins, Bertone-Johnson, Pekow, Carbone, & Chasan-Taber, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These same predictors, however, also increase the probability of reporting both alcohol and other illicit drug use, which often co-occur with smoking behaviors (Downs & Harrison, 1998;Simpson & Miller, 2002). Research has shown that persons who report the use of multiple substances are less likely to successfully quit smoking (Metrik, Spillane, Leventhal, & Kahler, 2011;Stapleton, Keaney, & Sutherland, 2009). Indeed, drinking and drug use may compromise individuals' resolve to quit smoking, particularly while under the influence of alcohol and other drugs, and increase exposure to tobacco.…”
Section: Factors Contributing To Smoking Among Smwmentioning
confidence: 99%
“…Adult co-users of tobacco and marijuana have an increased risk of developing nicotine dependence (Agrawal et al, 2012; Behrendt et al, 2009; Okoli et al, 2008; Timberlake et al, 2007; Tullis et al, 2003) and have worse tobacco cessation outcomes (Agrawal et al, 2012; Gourlay et al, 1994; Humfleet et al, 1999; Richter et al, 2002; Stapleton et al, 2009). While overall rates of tobacco use and co-use with marijuana are lower in adolescents compared with adults (Ramo et al, 2013), most addicted adults develop nicotine dependence during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both nicotine and cannabis affect similar pathways within the mesolimbic addiction pathways, suggesting similar and overlapping mechanisms for addiction (Filbey et al, 2009; Goldman et al, 2013). Finally, smoking cues are also similar between the two substances, which may contribute to the poorer tobacco cessation outcomes observed in adult co-users of marijuana (Agrawal et al, 2012; Gourlay et al, 1994; Humfleet et al, 1999; Stapleton et al, 2009). …”
Section: Introductionmentioning
confidence: 99%